Boundary Layer Characteristics over the Central Area of the Kathmandu Valley as Revealed by Sodar Observation - Shrestha, Sajan; Shrestha, Saraswati; Maharjan, Sangeeta; Regmi, Ram P. (Journal of Institute of Science and Technology, 2015)
The characteristic behavior of prevailing boundary layer over the central area of the Kathmandu valley was continuously monitored by deploying a monostatic flat array sodar during the period of 03 to 16 March 2013. Diurnal variation of wind and mixing layer height were chosen to describe the boundary layer activities over the area by considering the day of 12 March 2013 as the representative day for the period of observation. The study shows that central area of the valley remains calm or windless under stable stratification throughout the night and early morning frequently capped by northeasterly or easterly wind aloft. Strong surface level thermal inversion prevails during the period up to the height of 80m above the surface. This inversion tends to lift up as the morning progresses and reaches to the height of 875 m or so close to the noontime. Intrusion of regional winds as westerly/northwesterly and the southerly/southwesterly from the western and southwestern low-mountain passes and the river gorge in the afternoon tends to reduce the noontime mixing layer height to about 700 m. The diurnal variation of wind and mixing layer height suggest that Kathmandu valley possesses a poor air pollution dispersion power and hence the valley is predisposed to high air pollution potential. Journal of Institute of Science and Technology, 2015, 20(1): 28-35